2023
DOI: 10.3390/app13074206
|View full text |Cite
|
Sign up to set email alerts
|

Improving Structural Performance of Reinforced Concrete Beams with Phragmites Australis Fiber and Waste Glass Additives

Abstract: The construction industry has seen a growing emphasis on the use of sustainable materials in recent years. This is driven by various factors, including a desire to reduce environmental impact, improve indoor air quality, and promote the health and well-being of building occupants. One sustainable material that is being increasingly utilized in construction is natural fibers. Phragmites australis fibers, in particular, are renewable, biodegradable, and have a low carbon footprint. The present study aims to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Sustainable building materials, such as pervious planting concrete, which supports water permeability and urban vegetation, can help alleviate these issues. Moreover, sustainable building materials can be used in different types of concrete to reduce environmental impact, improve the relationship between humans and ecology, and promote the health and well-being of building occupants [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable building materials, such as pervious planting concrete, which supports water permeability and urban vegetation, can help alleviate these issues. Moreover, sustainable building materials can be used in different types of concrete to reduce environmental impact, improve the relationship between humans and ecology, and promote the health and well-being of building occupants [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…This slight drop in the UPV can be attributed to several factors. First of all, the presence of PhA fibers within the paste can lead to an increase in the number of voids, consequently leading to a UPV decrease [24,25]. In addition, it can be stated that various factors, such as the type and dimensions of the fibers, the orientation and dispersion of the fibers within the material, and the specific curing conditions, can all contribute to variations in the pulse velocity [38].…”
Section: Ultrasonic Pulse Velocity (Upv)mentioning
confidence: 99%
“…Consequently, recent studies have been directed towards investigating sustainable solutions, exploring the incorporation of such plant into construction materials, and assessing its potential effects in a more ecologically friendly manner. For example, a study demonstrated that incorporating 0.5% PhA fibers enhanced the load deflection of RC beams [24]. Furthermore, the results of another study revealed that the addition of PhA fibers of up to 2% resulted in a reduction in the shrinkage parameters [25].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the incorporation of 1.5% PA fibers in concrete significantly improved its capillary and water absorption properties [32]. In another study, it was demonstrated that the inclusion of Phragmites Australis plants in reinforced concrete beams resulted in improved performance, including increased load-carrying capacity and ductility compared to plain concrete beams [33]. These findings highlight the potential of using this plant as a beneficial reinforcement material for structural applications [34,35] To the best of the author's knowledge, there is hardly any research on volume stability and mechanical properties of mortar containing PA fibers, thus this paper aims to address these properties.…”
Section: Introductionmentioning
confidence: 98%